The Impact of Self-Esteem and Internet Use on Academic Performance - Juwono, Edhi; Winarta, I. Hardhy (Bina Nusantara University, 2017)
The students? academic performance is one of important evaluation factors in accreditation. It is interesting to explore the factors which give impact to the academic achievement or performance. This research put academic performance as the research problem. Since this research was combining two disciplines: information systems (IS) and educational management (EM), it set Internet Use (representing IS) and self-esteem (representing EM) as factors impacting the academic performance. Moreover, this research used the quantitative method. Based on the quantitative research model, the research used primary data collected from students of ABFI Institute of Perbanas, Jakarta. The data was calculated using a statistical tool called SPSS. The descriptive statistics was also applied to describe the variables, and regression technique was for describing the relationship between the variables. After analyzing the data, the research finds that self-esteem affects the academic performance significantly and positively, but the Internet use does not impact the academic performance significantly.